Genome-wide identification and characterization of long non-coding RNAs involved in acquired resistance to gefitinib in non-small-cell lung cancer. (August 2020) - Shi, Jingjing; Huang, Yutang; Wen, Chunjie; He, Shuai; Wu, Lanxiang; Zhou, Honghao
Graphical abstract: Highlights: Using RNA sequencing data to found lncRNAs and mRNA associated with acquired resistance to gefitinib in NSCLC. 39 lncRNAs and 121 mRNAs showed a consistent direction of dysregulation in both gefitinib-resistant NSCLC cell line pairs. LncRNA-mRNA network shows that several dysregulated lncRNAs are associated with the Hippo signaling pathway. Abstract: Acquired resistance is a major obstacle to the therapeutic efficacy of gefitinib in non-small-cell lung cancer (NSCLC). Current knowledge about the role of long non-coding RNAs (lncRNAs) in this phenomenon is insufficient. In this study, we searched RNA sequencing data for lncRNAs associated with acquired resistance to gefitinib in NSCLC, and constructed a functional lncRNA-mRNA co-expression network and protein-protein interaction (PPI) network to analyze their putative target genes and biological functions. The expression levels of 14 outstanding dysregulated lncRNAs and mRNA were verified using real-time PCR. Changes in the expression levels of 39 lncRNAs and 121 mRNAs showed common patterns in our two pairs of gefitinib-sensitive and gefitinib-resistant NSCLC cell lines. The co-expression network included 1235 connections among these common differentially expressed lncRNAs and mRNAs. The significantly enriched signaling pathways based on dysregulated mRNAs were mainly involved in the Hippo signaling pathway; proteoglycans in cancer; and valine, leucine, and isoleucine biosynthesis. The results show that LncRNAs play an important part in acquired gefitinib resistance in NSCLC by regulating mRNA expression and function, and may represent potential new molecular biomarkers and therapeutic targets for gefitinib-resistant NSCLC.